String quartet in F major, op. 18, no. 1 (score) - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Jean André; Offenbach am Main; Germany)
First edition of the score of the String Quartet no. 1 in F Major, op. 18, no. 1